Modelling the Stiffness Element in the Multi-Degree of Freedom Mass-Spring System - Bahari, Abdul Rahim; Rani, Muhamad Norhisham Abdul; Yunus, Mohd Azmi; Wan Iskandar Mirza, Wan Imaan Izhan; Shah, Mohd Azam Shah Aziz (Applied Mechanics and Materials, 2020)
Structural dynamics in structural engineering analysis involves the modal parameters (natural frequency, mode shape and damping ratio). The modal parameters of engineering structures is mainly influenced by the damping and stiffness properties. This research paper presents the reliability of CELAS element in the finite element modelling to represent the stiffness parameter. The simplified engineering structure considered in this study is a mass-spring system with multi-degree of freedom. Experimental modal testing is performed using an electro-magnetic vibration shaker as an exciter and an accelerometer to record the natural frequency of the system. HyperMesh normal mode analysis is used to compute the natural frequency of the mass-spring system. The comparative evaluation is performed in order to identify the accuracy of the natural frequencies obtained from the modelling analysis and the measured counterparts. Consequently, it is found that the element CELAS has a good capability to represent as the stiffness parameter in the finite element modelling.